Analysis Of Understanding Of Msme Activities In The Preparation Of Financial Statements Based On Sak EMKM And Cooperatives (Case Study Of Msmes In Ratu Agung District, Bengkulu City) - Elisa Fitri; Neri Susanti; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Data collection tools were carried out by means of documentation and unstructured interviews. The analytical method used is descriptif analysis. The results of research and discussion regarding the understanding of MSME actors in preparing financial statements based on SAK EMKM and Cooperatives on MSMEs in Ratu Agung District, Bengkulu City, especially in the Sawah Lebar sub-district, Bengkulu city, it can be concluded that MSME actors do not really understand financial statements in accordance with SAK EMKM and Cooperative. Of the 10 MSMEs interviewed, they only made simple reports such as recording sales notes in one day and did not make a recapitulation of financial reporting for one month and one year. This is due to the low level of understanding of MSME actors towards the preparation of financial reports. MSME actors have not separated personal wealth from business assets because they think that the assets they have are still small and there is no need for separation from assets used for business.